Caracterización del patrón proteico y perfil antigénico de larvas L3 de anisákidos de importancia médica aisladas de peces comerciales de la costa peruana - Martínez-Rojas, Rosa (2020)
Introduction. Anisakidosis is a zoonosis caused by accidental ingestion of anisakid larvae (L3). Objective. To characterize the protein pattern and antigenic profile of the L3 of Anisakis simplex s.l. (type I), A. physeteris s.l. (type II) and Contracaecum osculatum s.l. commercial fish isolated. Methods. An SDS-PAGE electrophoretic run of the somatic antigens was performed. Rabbits were immunized experimentally and evaluated by EITB. Results. The protein pattern of Anisakis type I showed 12 bands, 18 Anisakis type II and C. osculatum 13, with bands 10 and 35 kDa specific for Anisakis type II, 28 and 77 for C. osculatum, notpresent in Anisakis type I. Conclusion. Specific immunogenic bands were determined for Anisakis type I with the molecular weight proteins 11, 14, 25 and 40 kDa, for type II of 9, 10, 12, 35 and 41 kDa and C. osculatum 13, 15, 17, 30 and 47 kDa.